HPV epigenetic mechanisms related to Oropharyngeal and Cervix cancers. Issue 10 (3rd October 2018) - Di Domenico, Marina; Giovane, Giancarlo; Kouidhi, Soumaya; Iorio, Rosamaria; Romano, Maurizio; De Francesco, Francesco; Feola, Antonia; Siciliano, Camilla; Califano, Luigi; Giordano, Antonio
ABSTRACT: Human Papilloma Virus infection is very frequent in humans and is mainly transmitted sexually. The majority of infections are transient and asymptomatic, however, if the infection persists, it can occur with a variety of injuries to skin and mucous membranes, depending on the type of HPV involved. Some types of HPV are classified as high oncogenic risk as associated with the onset of cancer. The tumors most commonly associated with HPV are cervical and oropharyngeal cancer, epigenetic mechanisms related to HPV infection include methylation changes to host and viral DNA and chromatin modification in host species. This review is focused about epigenethic mechanism, such as MiRNAs expression, related to cervix and oral cancer. Specifically it discuss about molecular markers associated to a more aggressive phenotype. In this way we will analyze genes involved in meiotic sinaptonemal complex, transcriptional factors, of orthokeratins, sinaptogirin, they are all expressed in cancer in a way not more dependent on cell differentiation but HPV-dependent.